Pendekatan Sinergis dalam Penurunan Stunting di Desa Tumbang Baringei Melalui Pemanfaatan Ikan Patin Lokal - Sanjayanto Nugroho; Beklie Beklie; Reynu Dwi Kalvisa Noor; Beby Sulistya; Salma Aulia Putri Suherman; Siti Cahyani; Subhan Abdillah Aulia Rahman; Wesia Anrita Putri; Muhammad Aviedo Murel; Yulia Feronika; Hayyu Ananda; Yohana Yunita Klaudia; Elsa Sertani; Wahyu Prasetyo; Mauliyani Mauliyani; Tabita Marsella Kristian Hutagalung (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Stunting is a chronic nutritional problem that has serious impacts on children's physical, cognitive, and socio-emotional development, especially in Indonesia. This study aims to increase public awareness about stunting prevention through a socialization and intervention program in Tumbang Baringei Village, Gunung Mas Regency. This program involves KKN students, health workers, and educational institutions in various activities, including stunting socialization, cooking demonstrations of Supplementary Feeding (PMT) made from patin fish, and implementation of nutritious food provision in Kindergartens (TK). The results of the activities showed a significant increase in the knowledge and awareness of young mothers regarding the importance of balanced nutritional intake, as well as behavioral changes in maintaining children's health and nutrition. This intervention succeeded in building healthy eating habits from an early age and is expected to significantly reduce stunting rates in the village. In conclusion, cross-sector collaboration and empowerment of local communities are effective strategies in preventing stunting in Indonesia.